2019
DOI: 10.1111/bjir.12507
|View full text |Cite
|
Sign up to set email alerts
|

Towards a New Flashmob Unionism: The Case of theFight for 15Movement

Abstract: Unionism renewal has been described as a hybridization process between 'old' and 'new' logics. Understanding how these two potentially conflicting logics might be combined, however, has so far received little attention. Through the study of the Fight for 15 (FF15) movement, we investigate how the old 'collectivist' logic of action-oriented unions and the new 'connectivist' logic are being hybridized. To do so, we develop a mixed-methods approach that combines interviews with Twitter data. We evidence three m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 40 publications
2
50
0
1
Order By: Relevance
“…A crucial question concerns the relations likely to develop between conventional unions and such quasi-unions entering the labour market (Xhauflair et al 2018). Following Heckscher and Carré (2006) and Hyman and Gumbrell-McCormick (2017), building network institutions and joint activities within targeted campaigns could significantly increase their mutual influence, as evidenced by Pasquier et al (2020) in their in-depth study of the Fight for 15 Movement in the USA. Considering the relations between unions and quasi-unions, their respective strategic positioning and their struggle for legitimacy in a context of historical fragmentation often generate strong resistances against such network institutions (Heery et al 2012).…”
Section: The Growing Role Played By Third-party Actorsmentioning
confidence: 99%
“…A crucial question concerns the relations likely to develop between conventional unions and such quasi-unions entering the labour market (Xhauflair et al 2018). Following Heckscher and Carré (2006) and Hyman and Gumbrell-McCormick (2017), building network institutions and joint activities within targeted campaigns could significantly increase their mutual influence, as evidenced by Pasquier et al (2020) in their in-depth study of the Fight for 15 Movement in the USA. Considering the relations between unions and quasi-unions, their respective strategic positioning and their struggle for legitimacy in a context of historical fragmentation often generate strong resistances against such network institutions (Heery et al 2012).…”
Section: The Growing Role Played By Third-party Actorsmentioning
confidence: 99%
“…For trade unions, social media have brought new opportunities for innovative ways of mobilising, recruiting and communicating with members and of conducting political campaigns. The growing literature on trade unions’ use of social media has demonstrated that unions are employing a diverse set of social media platforms and that this usage varies across countries and trade unions (Panagiotopoulos, 2012; Rego et al ., 2014; Geelan, 2015; Hodder and Houghton, 2015; Scaramuzzino and Scaramuzzino, 2017; Barnes et al ., 2019; Jansson and Uba, 2019; Pasquier et al ., 2020). Researchers have examined trade unions’ social media use for recruitment (Jansson and Uba, 2019), mobilisation in wage negotiations (Wood and Pasquier, 2018) and industrial conflict (Upchurch and Grassman, 2016), and it has been argued that such varying usage is often related to the resources and leadership of trade unions (Panagiotopoulos and Barnett, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…As employers have strategically organized flexible networks, labor has begun networking (Maffie 2020; Pasquier et al 2020). Structurally, networks consist of a loose association of autonomous actors who coordinate through trust-based, lateral connections.…”
Section: Bargaining With Networked Employersmentioning
confidence: 99%
“…To do so, they often resort to nontraditional sources of power. In the Fight for $15 movement, a traditional labor union—the Service Employees International Union (SEIU)—joined grassroots organizations, and their network combined worker mobilization with aggressive social media activism to build symbolic power and take on a network of firms in the fast food sector (Pasquier, Daudigeos, and Barrios 2020). These actions, and others, have led to calls for examining how workers mobilize outside of traditional collective bargaining to improve employment conditions (Eaton, Schurman, and Chen 2017; Maffie 2020).…”
Section: Evolving Employment Relations Frameworkmentioning
confidence: 99%
See 1 more Smart Citation